(untitled) (Experimental biology, 2020)
This investigation is the part of more wide research program of Almaty region ecological factors effects on animal and human populations. Two territories were chosen as more polluted, where abandoned and destroyed storages of pesticides are present (Kyzyl Kayrat and Bes Kaynar villages in Talgar district) and more clean territory was used as control (Taukaraturyk village of Enbekshikazakh district). Besides pesticides toxical effect on human populations and animals can be produced by heavy metals penetrating into the human and animal organisms. This penetration is confirmed by their accumulation in the sheep wool. The collection of accumulated heavy metals, their absolute (mg/kg) and relative (comparing with other metals) concentrations in the sheep wool from polluted and control territories were the object of this investigation. These data supplement the knowledge about the ecotoxicology of the investigated territories. Microelements spectrum of sheep wool (Pb, Cd, Zn, Cu, Fe, Ni, Co, Mn, Cr) was studied using mineralization of 36 wool specimens and investigating them by Minotaur-2 microwave system according to PU 12=2009 method and atomic absorbtion spectrophotometer MGA-915. In the sheep wool from the control territory Cd, Co, Pb и Ni concentration is 13 times higher, Cr concentration is 6 times, and Cd, Co, Pb , Ni 2-3 times higher than in the soil, and only Cu concentration in the wool was 3 times lower, than in the soil. In the soils of polluted territories Zn concentration is 2-4 times higher than in control territory. In the wool from polluted territories Zn and Cu concentration is higher (3-4 times) than in the wool from control territory, in spite of the fact that in the both polluted soils Cu concentrations was not higher than in control territory soil. So Cu concentra-tion in the soil does not directly determine Cu concentration in the wool. Serious disturbances of metals concentrations range order in wool from polluted territories comparing with the order in wool from control territory is evident for Cu and Cd (higher concentration in polluted territories) while in the soils range order disturbance is evident for Cu and Pb (lower concentration in polluted territories). Large disturbances of range order of metals concentrations in the wool comparing with analogous order in soils of the same territories are evident for Cu (high concentration in soil and low in the wool) and for Cr (low concentration in the soil and high in the wool) both in the control territory. In the polluted territories the differences between range orders for the soil and wool were much less and the maximal is evident for Cu. So the factors determining Cu concentration in the soils and wool are unlike the factors of other metals concentrations.